Autonomy and self-esteem in handmade ceramic work: reflections on women's cooperativism in the Poti Velho neighborhood, in Teresina – Piauí (2006-2019): Autonomia e autoestima no trabalho cerâmico artesanal: reflexões sobre o cooperativismo feminino no bairro Poti Velho, em Teresina – Piauí (2006-2019) (Revista de História da UEG (REVHIST), 2022)
In this article, we analyze the experiences of women ceramic workers from Poti Velho, in Teresina - Piauí, with cooperativism (2006-2019). To do so, we will use the interviews done with five women from the Cooperative of Handicraft of Poti Velho (COOPERART-Poty). We seek to know the reflexes of the cooperativism in the lives of these women, in the formation of their identities as pottery workers and its contribution to the income and self-esteem of the women. We noticed that COOPERART-Poty had a relevant role in the constitution of women's identities as ceramics workers; the production of clay pieces increased their economic importance at home; and the ceramic work in the cooperative contributed to the development of women's self-esteem.Keywords: Ceramic work. Cooperativism. Women.